Editorial - Vedula, Krishna (Journal of Engineering Education Transformations, 2016)
It is my pleasure to introduce the October 2016 issue of JEET.As many of you already know, our goal is to strengthen the culture of engineering education research in institutions all over India. Thank you for your support in this endeavor.